Evaluation of Two Anorganic Bovine Xenogenous Grafts in Bone Healing of Critical Defect in Rats Calvaria - Garcia, Valdir Gouveia; Dall´agnol, Gizelli de Souza; Campista, Christian Cézane Cardoso; Bury, Luiz Lordêlo; Ervolino, Edilson [UNESP]; Longo, Mariéllen [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Levin, Liran; Theodoro, Letícia Helena [UNESP] (My University, 2024)
The purpose of this study was to provide an evaluation of two different xenogeneic bone substitutes in bone healing of critical-sized bone defects (Ø =5mm) created in rats calvaria. Thirty animals were randomized into 3 groups with one of the following treatments. In the control group (n=10), the defects were filled with blood clots; BO group (n=10), the defects were filled with bovine medullary bone substitute (Bio-Oss®); BF group (n=10), the defects were filled with bovine cortical bone substitute (Bonefill®). All defects were covered with an absorbable membrane. Five animals from each group were euthanized at 30 and 45 days, subsequently histomorphometrical and immunohistochemical analyses were performed. The histomorphometry was used to measure the percentage of new bone formation in the total area of the defect while the immunohistochemistry evaluated the expression of bone immunomarkers for bone morphogenetic protein 2/4 (BMP2/4), osteocalcin (OCN) and tartrate-resistant acid phosphatase (TRAP). Data was statistically analyzed with a 5% significance level. The results demonstrated that the BO group showed greater bone formation compared to the BF group at 30 days (P<0.05). However, there was no statistically significant difference between the control and BO groups at 30 days (P>0.05). The expression of BMP2/4 and OCN were higher in the BO group at 45 days compared to the BF at 30 and 45 days respectively (P<0.05). In conclusion, even with the higher expression of proteins related to bone formation, there was no difference in new bone formation at 45 days when both anorganic bovine xenogenous grafts were evaluated.
Keywords: Bone regeneration; bone substitutes; rats; wound healing; xenograft